Neuroprotective Effects of Kangen-karyu on Spatial Memory Impairment in an 8-Arm Radial Maze and Neuronal Death in the Hippocampal CA1 Region Induced by Repeated Cerebral Ischemia in Rats - Fengling Pu; Kyoko Motohashi; Tomohiro Kaneko; Yurika Tanaka; Naomi Manome; Keiichi Irie; Jirou Takata; Nobuaki Egashira; Ryozo Oishi; Takuya Okamoto; Yasuo Sei; Takako Yokozawa; et al. (Elsevier, 2009)
In the present study, we investigated the neuroprotective effects of Kangen-karyu (KGK) in a repeated cerebral ischemia model (2 × 10 min, 1-h interval). A 21-day pre- and postischemic treatment with KGK (10 - 300 mg/kg) and aspirin (5 mg/kg) improved the spatial memory impairment and neuronal death in the hippocampal CA1 region induced by repeated cerebral ischemia. However, a 7-day post-ischemic treatment with KGK did not attenuate the spatial memory impairment and neuronal death in this model. To determine the mechanism of action of KGK, we investigated the effects of a 14-day pre-ischemic treatment with KGK on cerebral blood flow in the hippocampal area of the repeated cerebral ischemia model using laser Doppler flowmetry. The 14-day pre-ischemic treatment with KGK increased the cerebral blood flow during reperfusion. These results suggest that a 21-day pre- and post-ischemic treatment with KGK can protect against brain damage caused by cerebral ischemia by increasing the cerebral blood flow in the hippocampal area. Keywords:: Kangen-karyu, repeated cerebral ischemia, cerebral blood flow, neuronal death